(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
Often family has the greatest influence on a person. And first of all, the personality of the child is formed. Parents help the child learn the rules of behavior in society, understand what is happening, communicate and interact with people, teach sympathy. The relationship between the child and the parents largely determines how he grows up, how he builds relationships with others. After all, the family puts on the child an example of behavior for the whole future life. Especially after the children reach the teenage age, more often they stop doing what their parents say. And this, according to the results of the study, usually occurs as a result of psychological changes and disorders in adolescents. In this article, opinions and comments are made about the life of adolescents, their views, family upbringing, family environment, the relationship of parents to their children and parents through the eyes of adolescents.